Türk romatoid artrit hastalarında IL-6 (interlökin-6) gen polimorfizmlerinin moleküler düzeyde incelenmesi - Sarıöz, Özlem (My University, 2009)
INVESTIGATION OF RHEUMATOID ARTHRITIS DISEASE AND IL-6 GENE POLYMORPHISMS IN MOLECULAR LEVEL Rheumatoid arthritis (RA) that is defined as the inflammation (swelling, moving difficulty and pain) in joints is common seen one of the rheumatological disorders. Although the ethiology of RA is not known completely, RA is accepted as multifactorial disease affected from genetics and environmental factors. The variations in HLA DR4 and HLA DR1 genes make genetic base for RA. The inflammaotory cytokines such as IL-1, TNF- α and IL-6 are produced at high level in painful cases such as RA. The variations in the prompoter of these genes may affect cytokin production. It has been shown that -174 C allele of IL-6 gene increased IL-6 level. In this study, the purpose of our research was to determine the type of variation of IL-6 for the risk factor in RA and to develop genetic test to detect early risk of RA in order to avoid the development of this disease in future. Our study, clinic tests were performed on people that are coming to RA Clinics of the Rheumatology Division of Marmara University for complaining joint pains. Genomic DNAs were isolated from 178 people diagnosed as RA based on these tests and 248 control. The promoter region of IL-6 gene was amplified using DNAs from patients and controls and their PCR products were digested by suitable enzymes. And then the variations in -174, 527, and -597 region of IL-6 were determined in both patients and control groups. The results of genetic analysis are : Any statistical relationship between RA and -174 geneotype distribution (p= 0,535) and -174 allele frequency (p =0,131) was not determined. Also, neither -572 genotype distrubition (p =0,570), nor -572 allele frequency (p =0, 876) of IL-6 showed any relationship with RA statistically. In addition to these results, there was no significant difference in -597 genotype distribution (p= 0,912) and allele frequency (p=0.506) of IL-6 between RA and control subjects.

TÜRK ROMATOİD ARTRİT HASTALARINDA IL-6 (İNTERLÖKİNGEN POLİMORFİZMLERİNİN MOLEKÜLER DÜZEYDE İNCELENMESİ Eklemlerde inflamasyon (şişme, hareket zorluğu ve ağrı) ile tanımlanan Romatoid Artrit (RA) hastalığı, sık görülen romatizmal hastalıklardan biridir. Romatoid artrit etyolojisi henüz tam olarak bilinmemekle birlikte genetik ve çevresel faktörlerden etkilenen çok nedenli bir hastalık olarak kabul edilir. HLA DR4 ve HLA DR1 genlerindeki varyasyonların romatoid artrite yatkınlığı, hastalığın genetik tabanını ortaya koymuştur. IL-1, TNF-α ve IL-6 gibi proinflamatuar sitokinler Romatoid artrit gibi ağrılı vakalarda yüksek seviyede üretilmektedir. Bu sitokinlerin genlerindeki çeşitli varyasyonlar sitokin üretim miktarını etkilemektedir. IL-6 geninin promoter bölgesinde tespit edilen -174 C alleli IL-6 seviyesini artırmaktadır. Bu nedenle bu çalışmada Türkiye’de IL-6’in hangi varyasyonunun RA için risk faktörü oluşturduğunu belirlemek ve ileride genetik test geliştirerek bu hastalık riskinin erken safhada belirlenebilmesi ile gelecekte bu hastalığın gelişiminin önlemesine katkı sağlamak amaçlanmıştır. Çalışmamızda Marmara Üniversitesi Araştırma Hastanesi Romatoloji Bölümü’ne eklem ağrısı şikayeti ile gelen kişilere klinik testler yapılmıştır. Bu testler doğrultusunda RA tanısı konan 178 hastadan ve kontrol grubunu oluşturan 248 sağlıklı kişiden genomik DNA izole edilmiştir. Bu DNA lar kullanılarak her hastanın IL-6 geninin promoter bölgesi PCR ile çoğaltılmış ve PCR ürünleri uygun enzimler ile kesilerek hasta ve kontrollerin IL-6 -174 ,-572 ,-597. pozisyonlarındaki varyasyonları belirlenmiştir. Genetik analizler sonucunda Romatoid Artrit hastalığı ile -174 genotip dağılımı (p=0,535), -174 allel frekansı arasında herhangi bir istatistiksel ilişki tespit edilmemiştir (p =0,131) . Romatoid Artrit hastalığı ile - 572 genotip dağılımı (p =0,570), -572 allel frekansı arasında anlamlı bir ilişkiye rastlanılmamıştır. Aynı şekilde -597 genotip dağılımları (p=0,912) ile -597 allel frekansları arasında da istatistiksel bir anlamlılık gözlenmemiştir.
Keywords: Romatoid Artrit Hastalığı